Primary extranodal classical Hodgkin lymphoma presenting as a chest wall mass mimicking tuberculosis: A rare case report with long-term follow-up (Indian Journal of Case Reports, 2026)
Classical Hodgkin lymphoma (CHL) is usually nodal, with primary extranodal disease being rare. Thoracic involvement without nodal disease is particularly unusual and may mimic tuberculosis (TB). We report the case of a 61-year-old male initially diagnosed with tubercular pleural effusion and treated with anti-tubercular therapy. Six months into treatment, he developed an intrathoracic mass. Imaging revealed extrapleural lesions involving the anterior chest wall muscle. Histopathology and immunohistochemistry confirmed CHL. He was staged IIAx and received 2 cycles adriamycin, bleomycin, vinblastine, dacarbazine, followed by 4 cycles adriamycin, etoposide, vinblastine, dacarbazine to avoid bleomycin toxicity, plus involved-field radiotherapy. He achieved a complete metabolic response and remains disease-free without long-term complications for 9 years. This case underscores the diagnostic challenges of primary extranodal CHL and the importance of thorough evaluation of atypical chest lesions, especially in TB -endemic regions.